High-voltage ceramic capacitor and application thereof

By introducing Si and preparing Ba(Ti0.5Zr0.2Sn0.2Ce0.1Si0.1)O3 as a dielectric material, combined with the use of modified binders, the problem of insufficient breakdown electric field of ceramic dielectric materials is solved, and high-voltage ceramic capacitors are realized The breakdown strength is significantly improved.

CN119340108AActive Publication Date: 2025-01-21KUNSHAN QINGYUAN ELECTRONIC TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411540552.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-21
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The breakdown electric field of existing ceramic dielectric materials is usually below 100 kV cm-1, which is difficult to meet the demand for high voltage of modern communication equipment, and the method of increasing the breakdown voltage by increasing the layer thickness has the problem of inefficiency.

Method used

By introducing SI, prepare BA (Ti0.5zr0.2sn0.2ce0.1si0.1) O3 as the electronics material and use modified adhesives. , Enhance the mechanical performance and power resistance of materials.

Benefits of technology

It is possible to significantly increase the breakdown strength of dielectric materials to more than 185kV/cm without increasing the layer thickness, meeting the high voltage requirements of modern communication equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340108A_ABST
    Figure CN119340108A_ABST
Patent Text Reader

Abstract

The invention provides a high-voltage ceramic capacitor and application thereof, and belongs to the technical field of capacitor materials, the high-voltage ceramic capacitor comprises a dielectric material, the chemical composition of the dielectric material is Ba (TimZrnSnpCeqSis) O3, m is greater than or equal to 0.5 and greater than or equal to 0.25, n is greater than or equal to 0.25 and greater than or equal to 0.2, p is greater than or equal to 0.25 and greater than or equal to 0.2, q is greater than or equal to 0.25 and greater than 0, s is greater than or equal to 0.1 and greater than 0, and m + n + p + q + s = 1. The layer thickness of the dielectric material is controlled to be 5-15 mm, and the breakdown strength is improved while the layer thickness is not increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of capacitor materials, and in particular relates to a high-voltage ceramic capacitor and application thereof. Background Art

[0002] With the miniaturization of mobile communication devices and the speed increase of CPU, the demand for capacitors is also gradually increasing. The core of capacitors is dielectric materials, among which ceramic dielectrics have the characteristics of large dielectric constant, low dielectric loss, large adjustability of dielectric properties and low temperature sensitivity. At present, they are increasingly used in scenarios such as high voltage, high capacitance and large ambient temperature span.

[0003] However, due to the limitation of extrinsic breakdown of ceramics, the breakdown electric field is usually around 100 kV cm -1 Therefore, to increase the breakdown voltage, it is necessary to increase the layer thickness. However, the requirements of modern communication equipment for miniaturization, portability, and lightness make increasing the layer thickness an effective but unwise approach. In addition, the improvement effect of increasing the layer thickness is also limited. Summary of the invention

[0004] In order to solve the problems existing in the background technology, the present invention provides a high-voltage ceramic capacitor and its application. The high-voltage ceramic capacitor includes a dielectric material with a layer thickness controlled at 5-15mm, which improves the breakdown strength without increasing the layer thickness.

[0005] In order to achieve the above-mentioned object, in a first aspect, the present invention provides a high voltage ceramic capacitor, comprising a dielectric material, the chemical composition of which is Ba(Ti m Zr n Sn p Ce q Si s )O3, where 0.5≥m≥0.25, 0.25≥n≥0.2, 0.25≥p≥0.2, 0.25≥q>0, 0.1≥s>0, and m+n+p+q+s=1.

[0006] Furthermore, the preparation method of the dielectric material is as follows:

[0007] S1, Ba(Ti m Zr n Sn p Ce q Si s ) barium carbonate, titanium oxide, zirconium oxide, tin oxide, cerium oxide and silicon dioxide required for O3 are mixed to obtain a premix;

[0008] S2, subjecting the premix obtained in S1 to a first ball milling treatment, calcining at 700-850°C for 3h, and then subjecting the premix to a second ball milling treatment to obtain a mixed powder;

[0009] S3, using a modified binder to press the mixed powder obtained in S2 into a disc with a thickness of 5-15 mm to obtain a green body;

[0010] S4. Sinter the green body obtained in S3 at 1100-1350°C for 2h, apply silver on the upper and lower surfaces, and then sinter at 800°C for 15min under nitrogen protection.

[0011] Furthermore, in S2, the first ball milling treatment conditions are: the mass ratio of ball milling medium to material is 5-6:1, the ball milling speed is 300-350r / min, and the ball milling time is 3-4h.

[0012] Furthermore, in S2, the second ball milling treatment conditions are: the mass ratio of ball milling medium to material is 7-8:1, the ball milling speed is 400-450r / min, and the ball milling time is 4-5h.

[0013] Furthermore, the ball milling media includes zirconium oxide beads or stainless steel balls.

[0014] Furthermore, the mass of the modified adhesive is 3-5% of the mass of the mixed powder.

[0015] Furthermore, the preparation method of the modified adhesive is as follows:

[0016] A1. Add 30g of polyvinyl alcohol into a 250mL three-necked flask equipped with a stirrer, then add 100-120mL of distilled water, and stir at 40-45°C for 15min to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol solution;

[0017] A2. Add 3 g of NaOH into a 100 mL beaker, dissolve it with 50-60 mL of distilled water, add 10-12 g of acrylic acid into the beaker under ice bath, stir evenly to obtain an acrylic acid solution;

[0018] A3, adding the polyvinyl alcohol solution obtained in A1 and the acrylic acid solution obtained in A2 into a three-necked flask equipped with a stirring device, introducing nitrogen gas at 35-40° C. and stirring evenly for 15 minutes to obtain a mixed solution; adding a crosslinking agent, an initiator and an initiation auxiliary agent to the mixed solution, raising the temperature to 50-55° C., reacting for 2-3 hours, the system becomes thick, aging for 30-40 minutes, taking out the product, washing it to neutrality, drying it, and crushing it to obtain a modified bonding powder;

[0019] A4. Dissolve or disperse the modified bonding powder obtained in A3 in water to form a 7% solution by mass to obtain a modified bonding agent.

[0020] Furthermore, in A3, the cross-linking agent is N,N'-methylenebisacrylamide, the initiator is potassium persulfate, and the initiation auxiliary is tetramethylethylenediamine.

[0021] Furthermore, the amount of the cross-linking agent is 0.6-0.7% of the mass of the mixed solution, the amount of the initiator is 0.5-0.6% of the mass of the mixed solution, and the amount of the initiation auxiliary is 0.1-0.2% of the mass of the mixed solution.

[0022] In a second aspect, the present invention provides an application of the above-mentioned high-voltage ceramic capacitor, which is used in power detection equipment and national grid equipment; in X-ray machines, CT machines, DC high-voltage generator medical equipment; and in electronic equipment in the communication field.

[0023] This application has the following beneficial effects:

[0024] 1. The present invention improves the breakdown strength of the dielectric material by introducing Si; improves the breakdown strength of the dielectric material by using a modified adhesive; and there is a synergistic effect between the two, which can synergistically improve the breakdown strength of the dielectric material.

[0025] 2. In the preparation of the modified adhesive of the present invention, polyvinyl alcohol and polyacrylic acid (acrylic acid polymerization) achieve cohesion through high hydrogen bond density and physical entanglement of polymer chains. This three-dimensional network structure can not only enhance the mechanical properties of the material, but also effectively block the current path and improve the breakdown voltage; the abundant non-composite hydroxyl and carboxylic acid groups can also establish a variety of interactions with the surface of the adherend, including hydrogen bonds, coordination bonds and van der Waals forces. These strong interfacial interactions also help to improve the electrical strength of the material. The incorporation of nano-silica can effectively improve the tensile bonding strength, so that the modified adhesive can more effectively disperse the stress throughout the material, reduce the breakdown risk caused by stress concentration, and thus achieve the effect of improving the breakdown strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 , a comparative trend chart of the breakdown strength test data of the materials obtained in Examples 1-5 of the present invention and Comparative Examples 1-4. DETAILED DESCRIPTION

[0027] The present application is further described in detail below with reference to the embodiments.

[0028] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0029] Example 1: (1) A modified adhesive is prepared, and the preparation method thereof is as follows:

[0030] A1. Add 30 g of polyvinyl alcohol into a 250 mL three-necked flask equipped with a stirrer, then add 110 mL of distilled water, and stir at 130 r / min for 15 min at 42 °C to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol solution.

[0031] A2. Add 3 g of NaOH into a 100 mL beaker and dissolve it with 55 mL of distilled water. Add 11 g of acrylic acid into the beaker under ice bath and stir at 120 r / min for 10 min. Stir evenly to obtain an acrylic acid solution.

[0032] A3. Add the polyvinyl alcohol solution obtained in A1 and the acrylic acid solution obtained in A2 into a three-necked flask equipped with a stirring device, introduce nitrogen at 38°C and stir at a constant speed of 100 r / min for 15 min to obtain a mixed solution.

[0033] Add crosslinking agent N, N'-methylenebisacrylamide, initiator potassium persulfate and initiation auxiliary agent tetramethylethylenediamine to the mixed solution. The amount of crosslinking agent is 0.65% of the mass of the mixed solution, the amount of initiator is 0.55% of the mass of the mixed solution, and the amount of initiation auxiliary agent is 0.15% of the mass of the mixed solution.

[0034] Then, the temperature was raised to 52°C, and the reaction was continued with stirring at a constant speed of 100 r / min for 2.5 hours. When the system became thick, the stirring was stopped, and the mixture was aged for 35 minutes, and the product was filtered out. The product was washed with ethanol, air-dried, and then soaked in distilled water for seven days. The water was changed at regular intervals to wash away the residual monomers and other soluble substances in the reaction product, so that the pH value of the product was 7. The product was placed in an oven for drying and crushed to obtain a modified bonding powder.

[0035] A4. Dissolve or disperse the modified bonding powder obtained in A3 in water to form a 7% solution by mass to obtain the modified bonding agent. The specific dissolution or dispersion method is: put the modified bonding powder into water, stir at a constant speed of 120r / min for 5 minutes, then increase the speed to 180r / min and stir at a constant speed for 10 minutes, then reduce the speed to 100r / min and stir at a constant speed for 5 minutes.

[0036] Polyvinyl alcohol PVA124 (Kuraray, Japan) was purchased from Guangzhou Qihua Chemical Co., Ltd. Acrylic acid was purchased from Shanghai Chemical Industry Co., Ltd. of China National Pharmaceutical Group Corporation N,N'-methylenebisacrylamide (industrial grade) was purchased from Zhengzhou Taixin Chemical Products Co., Ltd. Potassium persulfate was purchased from Shandong Jiaying Chemical Technology Co., Ltd. Tetramethylethylenediamine was purchased from Jinan Huifengda Chemical Co., Ltd.

[0037] (2) A dielectric material is prepared, and the preparation method is as follows:

[0038] S1, Ba(Ti 0.4Zr 0.2 Sn 0.2 Ce 0.1 Si 0.1 )The barium carbonate, titanium oxide, zirconium oxide, tin oxide, cerium oxide and nano silicon dioxide required for O3 are mixed to obtain a premix.

[0039] S2. The premix obtained in S1 is subjected to a first ball milling treatment, calcined at 800° C. for 3 h, and then subjected to a second ball milling treatment to obtain a mixed powder.

[0040] The first ball milling treatment conditions were: the mass ratio of the ball milling medium to the material was 5.5:1, the ball milling speed was 320r / min, and the ball milling time was 3.5h. The second ball milling treatment conditions were: the mass ratio of the ball milling medium to the material was 7.5:1, the ball milling speed was 420r / min, and the ball milling time was 4.5h. The ball milling medium was zirconia beads with a diameter of 1.5mm.

[0041] S3. Using the modified binder prepared in (1), the mixed powder obtained in S2 is pressed into a disc with a thickness of 10 mm to obtain a green body. The mass of the modified binder is 4% of the mass of the mixed powder.

[0042] S4. After sintering the green body obtained in S3 at 1200° C. for 2 hours, silver is applied to the upper and lower surfaces, and then sintered at 800° C. for 15 minutes under nitrogen protection to obtain the dielectric material.

[0043] A high-voltage ceramic capacitor comprises the dielectric material prepared above.

[0044] Example 2: The difference between this example and Example 1 is that: (1) a modified adhesive is prepared, and the preparation method thereof is as follows:

[0045] A1. Add 30 g of polyvinyl alcohol into a 250 mL three-necked flask equipped with a stirrer, then add 100 mL of distilled water, and stir at 130 r / min for 15 min at 40°C to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol solution.

[0046] A2. Add 3 g of NaOH into a 100 mL beaker and dissolve it with 50 mL of distilled water. Add 10 g of acrylic acid into the beaker under ice bath and stir at 120 r / min for 10 min. Stir evenly to obtain an acrylic acid solution.

[0047] A3. Add the polyvinyl alcohol solution obtained in A1 and the acrylic acid solution obtained in A2 into a three-necked flask equipped with a stirring device, introduce nitrogen at 35°C and stir at a constant speed of 100 r / min for 15 min to obtain a mixed solution.

[0048] Add crosslinking agent N,N'-methylenebisacrylamide, initiator potassium persulfate and initiation auxiliary agent tetramethylethylenediamine to the mixed solution. The amount of crosslinking agent is 0.6% of the mass of the mixed solution, the amount of initiator is 0.5% of the mass of the mixed solution, and the amount of initiation auxiliary agent is 0.1% of the mass of the mixed solution.

[0049] Then, the temperature was raised to 50°C, and the reaction was continued with stirring at a constant speed of 100 r / min for 2 hours. When the system became thick, the stirring was stopped, and the product was aged for 30 minutes, and the product was filtered out; the product was washed with ethanol, air-dried, and then soaked in distilled water for seven days. The water was changed at regular intervals to wash away the residual monomers and other soluble substances in the reaction product, so that the pH value of the product was 7; the product was placed in an oven for drying and crushed to obtain a modified bonding powder.

[0050] A4. Dissolve or disperse the modified bonding powder obtained in A3 in water to form a 7% solution by mass to obtain a modified bonding agent.

[0051] Example 3: The difference between this example and Example 1 is that: (1) a modified adhesive is prepared, and the preparation method thereof is as follows:

[0052] A1. Add 30 g of polyvinyl alcohol into a 250 mL three-necked flask equipped with a stirrer, then add 120 mL of distilled water, and stir at 45 °C and 130 r / min for 15 min to completely dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol solution.

[0053] A2. Add 3 g of NaOH into a 100 mL beaker and dissolve it with 60 mL of distilled water. Add 12 g of acrylic acid into the beaker under ice bath and stir at 120 r / min for 10 min. Stir evenly to obtain an acrylic acid solution.

[0054] A3. Add the polyvinyl alcohol solution obtained in A1 and the acrylic acid solution obtained in A2 into a three-necked flask equipped with a stirring device, introduce nitrogen at 40°C and stir at a constant speed of 100 r / min for 15 min to obtain a mixed solution.

[0055] Add crosslinking agent N,N'-methylenebisacrylamide, initiator potassium persulfate and initiation auxiliary agent tetramethylethylenediamine to the mixed solution. The amount of crosslinking agent is 0.7% of the mass of the mixed solution, the amount of initiator is 0.6% of the mass of the mixed solution, and the amount of initiation auxiliary agent is 0.2% of the mass of the mixed solution.

[0056] Then, the temperature was raised to 55°C, and the reaction was continued with stirring at a constant speed of 100 r / min for 3 hours. When the system became thick, the stirring was stopped, and the system was aged for 40 minutes, and the product was filtered out; the product was washed with ethanol, air-dried, and then soaked in distilled water for seven days. The water was changed at regular intervals to wash away the residual monomers and other soluble substances in the reaction product, so that the pH value of the product was 7; the product was placed in an oven for drying and crushed to obtain a modified bonding powder.

[0057] A4. Dissolve or disperse the modified bonding powder obtained in A3 in water to form a 7% solution by mass to obtain a modified bonding agent.

[0058] Example 4: The difference between this example and Example 1 is that: (2) a dielectric material is prepared, and the preparation method thereof is as follows:

[0059] S1, Ba(Ti 0.25 Zr 0.25 Sn 0.25 Ce 0.2 Si 0.05 )The barium carbonate, titanium oxide, zirconium oxide, tin oxide, cerium oxide and silicon dioxide required for O3 are mixed to obtain a premix.

[0060] S2. The premix obtained in S1 is subjected to a first ball milling treatment, calcined at 800° C. for 3 h, and then subjected to a second ball milling treatment to obtain a mixed powder.

[0061] The first ball milling treatment conditions were: the mass ratio of the ball milling medium to the material was 5:1, the ball milling speed was 350r / min, and the ball milling time was 3h. The second ball milling treatment conditions were: the mass ratio of the ball milling medium to the material was 7:1, the ball milling speed was 400r / min, and the ball milling time was 4h. The ball milling medium was zirconia beads.

[0062] S3, using a modified binder to press the mixed powder obtained in S2 into a disc with a thickness of 10 mm to obtain a green body. The mass of the modified binder is 4% of the mass of the mixed powder.

[0063] S4. After sintering the green body obtained in S3 at 1150°C for 2 hours, silver is applied to the upper and lower surfaces, and then sintered at 800°C for 15 minutes under nitrogen protection to obtain the dielectric material.

[0064] Embodiment 5: The difference between this embodiment and embodiment 1 is that: (2) a dielectric material is prepared, and the preparation method thereof is as follows:

[0065] S1, Ba(Ti 0.5 Zr 0.2 Sn 0.2 Ce 0.05 Si 0.05)The barium carbonate, titanium oxide, zirconium oxide, tin oxide, cerium oxide and silicon dioxide required for O3 are mixed to obtain a premix.

[0066] S2. The premix obtained in S1 is subjected to a first ball milling treatment, calcined at 850° C. for 3 h, and then subjected to a second ball milling treatment to obtain a mixed powder.

[0067] The first ball milling treatment conditions were: the mass ratio of the ball milling medium to the material was 6:1, the ball milling speed was 350r / min, and the ball milling time was 4h. The second ball milling treatment conditions were: the mass ratio of the ball milling medium to the material was 8:1, the ball milling speed was 450r / min, and the ball milling time was 5h. The ball milling medium was zirconia beads.

[0068] S3, using a modified binder to press the mixed powder obtained in S2 into a disc with a thickness of 10 mm to obtain a green body. The mass of the modified binder is 4% of the mass of the mixed powder.

[0069] S4. After sintering the green body obtained in S3 at 1300° C. for 2 hours, silver is applied on the upper and lower surfaces, and then sintered at 800° C. for 15 minutes under nitrogen protection to obtain the dielectric material.

[0070] Comparative Example 1: The difference between this comparative example and Example 1 is that in the preparation of the dielectric material, Si is deleted, that is, nano-silicon dioxide is deleted.

[0071] Specifically, in the preparation of a dielectric material, S1, Ba(Ti 0.4 Zr 0.2 Sn 0.2 Ce 0.1 )The barium carbonate, titanium oxide, zirconium oxide, tin oxide and cerium oxide required for O3 are mixed to obtain a premix.

[0072] Comparative Example 2: The difference between this comparative example and Example 1 is that the modified adhesive is replaced by a common commercially available PVA adhesive.

[0073] The common commercially available PVA adhesive (solid content 18±1%) was purchased from Wuxi Qianzhou Coating Material Factory. When used, it was first made into a solid content of 7% with water before use.

[0074] Comparative Example 3: The difference between this comparative example and Example 1 is that: in the preparation of the dielectric material, Si is deleted; and the modified adhesive is replaced with a common commercially available PVA adhesive.

[0075] Specifically, in the preparation of a dielectric material, S1, Ba(Ti 0.4 Zr 0.2 Sn 0.2 Ce 0.1)The barium carbonate, titanium oxide, zirconium oxide, tin oxide and cerium oxide required for O3 are mixed to obtain a premix.

[0076] In addition, common commercially available PVA adhesive (solid content 18±1%) was purchased from Wuxi Qianzhou Coating Material Factory. When used, it was first made into a solid content of 7% with water before use.

[0077] Comparative Example 4: The difference between this comparative example and Example 1 is that in the preparation of the dielectric material, an equal amount of nano-silicon dioxide is used in the preparation of the modified adhesive.

[0078] Specifically, in the preparation of a dielectric material, S1, Ba(Ti 0.4 Zr 0.2 Sn 0.2 Ce 0.1 Si 0.1 ) The barium carbonate, titanium oxide, zirconium oxide, tin oxide, cerium oxide and nano silicon dioxide required for O3 are mixed evenly except nano silicon dioxide to obtain a premix. The nano silicon dioxide is reserved for later use.

[0079] In addition, the reserved nano-silicon dioxide is used in the preparation process of the modified adhesive, specifically, added together with the polyvinyl alcohol solution obtained from A1 and the acrylic acid solution obtained from A2.

[0080] Test Example: The breakdown strength of the dielectric materials obtained in Examples 1-5 and Comparative Examples 1-4 is shown in Tables 1 and Figure 1 .

[0081] Table 1. Test data of the experimental example

[0082] Breakdown strength (kV / cm) Example 1 188 Example 2 190 Example 3 192 Example 4 186 Example 5 185 Comparative Example 1 171 Comparative Example 2 160 Comparative Example 3 151 Comparative Example 4 179

[0083] Test conclusion: Analyze the examples 1-5 and combine the data in Table 1 and Figure 1 It can be seen that the breakdown strength of the dielectric material prepared by the present invention is as high as 185 kV / cm or more.

[0084] Analyze Example 1 and Comparative Examples 1-3 and combine the data in Table 1 and Figure 1 It can be seen that the introduction of Si can improve the breakdown strength of the obtained dielectric material; replacing the commercially available PVA adhesive with the homemade modified adhesive of the present invention can also improve the breakdown strength of the obtained dielectric material; and there is a synergistic effect between the two, which can synergistically improve the breakdown strength of the obtained dielectric material.

[0085] Analyze Example 1 and Comparative Example 4 and combine the data in Table 1 and Figure 1It can be seen that compared with Example 1, Comparative Example 4 changes the way of introducing Si by directly introducing Si in the process of preparing the modified adhesive. As a result, the breakdown strength of the obtained dielectric material decreases instead of increases.

[0086] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0087] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A high voltage ceramic capacitor, characterized in that: Including dielectric material, the chemical composition of which is Ba(Ti m Zr n Sn p Ce q Si s )O3, where 0.5≥m≥0.25, 0.25≥n≥0.2, 0.25≥p≥0.2, 0.25≥q>0, 0.1≥s>0, and m+n+p+q+s=1.

2. The high voltage ceramic capacitor according to claim 1, characterized in that: The preparation method of the dielectric material is as follows: S1, Ba(Ti m Zr n Sn p Ce q Si s ) barium carbonate, titanium oxide, zirconium oxide, tin oxide, cerium oxide and silicon dioxide required for O3 are mixed to obtain a premix; S2, subjecting the premix obtained in S1 to a first ball milling treatment, calcining at 700-850°C for 3h, and then subjecting the premix to a second ball milling treatment to obtain a mixed powder; S3, using a modified binder to press the mixed powder obtained in S2 into a disc with a thickness of 5-15 mm to obtain a green body; S4. Sinter the green body obtained in S3 at 1100-1350°C for 2h, apply silver on the upper and lower surfaces, and then sinter at 800°C for 15min under nitrogen protection.

3. The high voltage ceramic capacitor according to claim 2, characterized in that: In S2, the first ball milling treatment conditions are: the mass ratio of ball milling medium to material is 5-6:1, the ball milling speed is 300-350r / min, and the ball milling time is 3-4h.

4. The high voltage ceramic capacitor according to claim 3, characterized in that: In S2, the second ball milling treatment conditions are: the mass ratio of ball milling medium to material is 7-8:1, the ball milling speed is 400-450r / min, and the ball milling time is 4-5h.

5. The high voltage ceramic capacitor according to claim 3 or 4, characterized in that: The ball milling media include zirconia beads or stainless steel balls.

6. The high voltage ceramic capacitor according to claim 2, characterized in that: The mass of the modified adhesive is 3-5% of the mass of the mixed powder.

7. The high voltage ceramic capacitor according to claim 2 or 6, characterized in that: The preparation method of the modified adhesive is as follows: A1. Add 30g polyvinyl alcohol into a 250mL three-necked flask, then add 100-120mL distilled water, and stir at 40-45°C for 15min to obtain a polyvinyl alcohol solution; A2. Add 3 g of NaOH into a 100 mL beaker, then add 50-60 mL of distilled water, add 10-12 g of acrylic acid under ice bath, stir evenly to obtain an acrylic acid solution; A3, adding the polyvinyl alcohol solution obtained in A1 and the acrylic acid solution obtained in A2 into a three-necked flask, introducing nitrogen at 35-40° C. and stirring for 15 minutes to obtain a mixed solution; adding a crosslinking agent, an initiator and an initiation auxiliary agent to the mixed solution, heating to 50-55° C., reacting for 2-3 hours, aging for 30-40 minutes, washing the product to neutrality, drying, and crushing to obtain a modified bonding powder; A4. Dissolve or disperse the modified bonding powder obtained in A3 in water to form a 7% solution by mass to obtain a modified bonding agent.

8. The high voltage ceramic capacitor according to claim 7, characterized in that: In A3, the cross-linking agent is N,N'-methylenebisacrylamide, the initiator is potassium persulfate, and the initiation auxiliary is tetramethylethylenediamine.

9. The high voltage ceramic capacitor according to claim 8, characterized in that: The amount of the cross-linking agent is 0.6-0.7% of the mass of the mixed liquid, the amount of the initiator is 0.5-0.6% of the mass of the mixed liquid, and the amount of the initiation auxiliary agent is 0.1-0.2% of the mass of the mixed liquid.

10. An application of a high voltage ceramic capacitor according to any one of claims 1 to 9, characterized in that: Used in power detection equipment and national grid equipment; used in X-ray machines, CT machines, DC high voltage generator medical equipment; used in electronic equipment in the communication field.

Citation Information

Patent Citations

  • Method for preparing and modifying polyacrylic acid super-absorbent resin

    CN102161725A

  • Dielectric material for ceramic capacitor and preparation method of dielectric material

    CN105272233A

  • Binder, preparation method of binder, electrode plate and secondary battery

    CN112680148A

  • High-voltage ceramic capacitor medium for microwave oven magnetron

    CN1545113A